A Tribute to Elliot S. Vesell (1933–2018). (November 2018) - Nebert, Daniel W.
Abstract : The field of pharmacogenetics and pharmacogenomics was greatly saddened by the recent loss of one of its founders and giants in this research area. Elliot S. Vesell – Emeritus and Evan Pugh Professor of the Department of Pharmacology, Penn State College of Medicine, Hershey, PA, USA – passed away 23 July 2018 at age 84.